Manajemen Pengadaan Bahan Baku Tandan Buah Segar (TBS) di Pabrik Kelapa Sawit (Studi Kasus di PT Katingan Indah Utama Kotawaringin Timur Kalimantan Tengah) - Fitra Darmawan; Tri Endar Suswatiningsih; Christina Wahyu Ary Dewi (Program Studi Agribisnis INSTIPER Yogyakarta, 2022)
The aims of the study are 1) Examine the management of FFB raw material procurement in PPKS, 2) calculate the utilization of used capacity from installed capacity on PPKS, 3) analyze the obstacles that arise in the process of fulfilling FFB raw materials in PPKS. This research method is case study research method. Sampling using a key person. Data analysis is done by calculating the used capacity. The results showed that the management of the procurement of raw material for fresh fruit bunches was carried out by planning a system for one year of production based on the RKT (Annual Work Plan), organizing raw materials for fresh fruit bunches from internal plantations and external plantations and the implementation and supervision carried out were very good. seen from the average number of realizations. Utilization of the actual used capacity of Kabuau PPKS is fairly good, with an average of 85.55% of the factory's installed capacity. The obstacle faced in procuring FFB raw materials at Kabuau PPKS from internal plantations is the lack of smooth delivery of fruit. The external constraint is the supply of fruit that is not of good quality. Keywords: management, procurement, used capasity